International Conference on Space Optics — ICSO 2018 2019
DOI: 10.1117/12.2536075
|View full text |Cite
|
Sign up to set email alerts
|

High-speed low-power and board-mountable optical transceivers for scalable & energy efficient advanced on‐board digital processors

Abstract: We present the development and verification testing of a high speed multimode, multicore transceiver technology for intra-satellite optical interconnects. We report the fabrication and functional testing of opto-parts including 25 Gb/s 850 nm VCSEL/PD as well as the verification testing of the VCSELs against radiation and lifetime performance. In addition we report the development and evaluation testing of a multi-core cable assembly that was fabricated and mated with MiniAVIM multi-core connectors to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…By optimizing the fiber fabrication and cabling process, the transmission loss, XT and BER performance will be further improved. In the future, combined with an MCF connector, MCF transceiver and low-loss splicing of MCF [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 30 , 31 ], the prepared ultra-bend-resistant 4-core SXC would have potential applications to further release the space pressure, reduce power consumption and improve the transmission capacity on short-reach DSDM optical transmission. Furthermore, by using plasmonic material as fiber coating, the 4-core fiber may also be extended in the industry for applications in advanced sensors, surface-enhanced Raman spectroscopy and so on [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By optimizing the fiber fabrication and cabling process, the transmission loss, XT and BER performance will be further improved. In the future, combined with an MCF connector, MCF transceiver and low-loss splicing of MCF [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 30 , 31 ], the prepared ultra-bend-resistant 4-core SXC would have potential applications to further release the space pressure, reduce power consumption and improve the transmission capacity on short-reach DSDM optical transmission. Furthermore, by using plasmonic material as fiber coating, the 4-core fiber may also be extended in the industry for applications in advanced sensors, surface-enhanced Raman spectroscopy and so on [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods need to use numerous SC-SMF SXCs or ribbon cables to achieve the OI between thousands of conventional optical modules and fan-in/fan-out (FIFO) devices, which will cause space congestion in DC [ 1 , 7 , 8 ]. By using an MCF-SXC and combining it with an MCF connector and MCF optical transceiver [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], it can provide an optimal solution to further release the space pressure, save power consumption and increase the access density on OI in DC [ 12 , 13 ]. But there are few studies on the manufacture process and transmission characteristics of the MCF-SXC.…”
Section: Introductionmentioning
confidence: 99%
“…Since DTP5G, high-speed electrical interconnects have been replaced by optical interconnects [1,2,3,4]. On DTP5G, optical transceivers working at high speed data rate higher than 10 Gbps were introduced after a selection and qualification process [5,6,8]. Needs for even higher data rates over more links with optimized mass and power budgets for DTP6G led to a reassessment of the optical interconnect architecture and the selection of new transceiver operating at data rates higher than 20 Gbps.…”
Section: On Board Digital Transparent Processormentioning
confidence: 99%
“…Compared with the state-of-the-art literature, the packaged 4 × 10 Gbps transceiver in Karppinen et al [6] achieved 40 Gbps with an energy efficiency of 4.5 mW/Gbps per channel. The 2 × 3 × 25 Gbps integrated transmitters and receivers in Stampoulidis et al [8] demonstrated a 17.5 Gbps error-free performance for a total of 107 Gbps and energy efficiency of 6.26 mW/Gbps when packaged on a demonstrator board. The proposed differential transceiver with fully integrated mid-board optics achieved an energy efficiency of <6 mW/Gb/s for the entire link at 112 Gb/s transmission which is the highest reported data rate from a single ASIC and, to the best knowledge of the authors, the first with pluggable mid-board optics featuring custom build RH ICs.…”
Section: Comparison With Literaturementioning
confidence: 99%
“…The state-of-the-art literature presents a 4 × 10 Gbps ASIC VCSEL-based transceiver operating on the "SpaceFibre" standard demonstrated by Karppinen et al [6]. Additionally, Ko et al demonstrated a 3 × 25 Gbps VCSEL-based transceiver ASIC with separate 3 × 25 single-ended receiver and 3 × 25 singleended transmitter sub-assemblies [7], which was subsequently integrated into a 6 × 25 Gbps module [8].…”
Section: Introductionmentioning
confidence: 99%